A Review on Machine Learning and Its Applications (International Journal of Innovative Research in Computer Science & Technology, 2022)
Learning is the most important aspect of  human intellect and the most fundamental method of  acquiring information. Machine learning is the most basic  method for making a machine intelligent. Application Data  has grown in quantity over the last several decades,  necessitating the need to uncover anything that might lead  to critical judgments, so deep learning is assisting much in  this regard. It's a subset of artificial intelligence that allows  machines to learn by experience or example in the same  way that people do, and to discover fascinating patterns  without having to be programmed. The algorithm is fed  data, which is then used to create a model. It can forecast  new values using this model. It assists us in locating  something unfamiliar to us, which may lead to the  discovery of many new experiences. Health,  finance, travel, retail, image processing, media and video  processing, natural language, computerized trading,  automobile, aerospace, manufacturing, or a variety of other  areas may all benefit from machine learning. This article  presents an overview of machine learning's fundamentals,  techniques, including applications in numerous industries.
Keywords: Algorithms; Machine Learning; Supervised Learning; Unsupervised Learning